Examining Jurors: Applying Conversation Analysis to Voir Dire in Capital Cases, a First Look - Grosso, Catherine M. (2017)
Scholarship about racial disparities in jury selection is extensive, but the data about how parties examine potential jurors in actual trials is limited. This study of jury selection for 792 potential jurors across twelve randomly selected North Carolina capital cases uses conversation analysis to examine the process that produces decisions about who serves on juries. To examine how race influences conversations in voir dire, we adapted the Roter Interaction Analysis System, a widely used framework for understanding the dynamics of patient–clinician communication during clinical encounters, to the legal setting for the first time. This method allows us to document the conversational dynamics of actual questioning of potential jurors that precedes the decision to seat or strike a juror, or to excuse her for cause. Our preliminary analysis of this uniquely rich archival data suggests ways in which the discourse of jury selection varies by race, and provides the foundation for future work looking at the ways in which the evaluation of fitness for jury service itself is skewed and contributes to racial disparities in jury selection